2008
DOI: 10.1016/j.jchromb.2008.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a gas chromatography–mass spectrometry method for the analysis of sterol oxidation products in serum

Abstract: A validated gas chromatography-mass spectrometry (GC-MS) detection method for the quantitative analysis of sterol oxidation products (SOPs) in serum is described. After a lipid extraction procedure with chloroform/methanol, a cold saponification and purification by solid phase extraction, oxysterols were derivatizated to form trimethyl-sylil-ethers which were subjected to GC-MS analysis. Calibration curves for cholesterol oxidation products showed determination coefficient (R 2 ) of 1.0, with low values for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 41 publications
(46 reference statements)
2
33
1
2
Order By: Relevance
“…β-epoxysitostanol and sitostanetriol were the most abundant, while campestanetriol, α-epoxysitostanol, 7-ketositosterol and 7β-hydroxysitosterol concentrations were lower. Menéndez-Carreño et al (2008a) found 7α-hydroxysitosterol (47.3 ng/mL) and 7β-hydroxysitosterol (49.0 ng/mL) in the serum of healthy volunteers.…”
Section: Introductionmentioning
confidence: 91%
“…β-epoxysitostanol and sitostanetriol were the most abundant, while campestanetriol, α-epoxysitostanol, 7-ketositosterol and 7β-hydroxysitosterol concentrations were lower. Menéndez-Carreño et al (2008a) found 7α-hydroxysitosterol (47.3 ng/mL) and 7β-hydroxysitosterol (49.0 ng/mL) in the serum of healthy volunteers.…”
Section: Introductionmentioning
confidence: 91%
“…The sample solutions of cholesterol and stigmasterol oxidation products were derivatized to trimethylsilyl (TMS) ethers. Their chromatographic analysis, identification and quantification were performed according to the validated method of Menéndez-Carreño et al [25]. Calibration curves of COPs were also used to quantify StOPs, as it has been demonstrated that the response factor obtained for cholesterol oxidation products are also valid for quantitative work regarding phytosterol oxidation products [26].…”
Section: Sterol Oxidation Products Determinationmentioning
confidence: 99%
“…To date, quantifi cation of oxysterols in biological samples has been accomplished principally using GC-MS methods (14)(15)(16)(17)(18). Although this technique provides sensitive detection of oxysterols in complex mixtures, GC-MSbased methods are hampered by labor-intensive sample preparation and extraction procedures and by requirement for relatively large plasma volumes.…”
Section: Lc-ms/ms Analysismentioning
confidence: 99%